2020
DOI: 10.1074/jbc.ra120.014603
|View full text |Cite
|
Sign up to set email alerts
|

Complex I mutations synergize to worsen the phenotypic expression of Leber's hereditary optic neuropathy

Abstract: Leber’s hereditary optic neuropathy (LHON) is a maternal inheritance of eye disease due to the mitochondrial DNA mtDNA) mutations. We previously discovered a 3866T>C mutation within the gene for the ND1 subunit of complex I as possibly amplifying disease progression for patients bearing the disease-causing 11778G>A mutation, within the gene for the ND4 subunit of Complex I. However, whether and how the ND1 mutation exacerbates the ND4 mutation were unknown. In this report, we showed that four Chinese fam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 78 publications
1
36
0
Order By: Relevance
“…To investigate if the m.4295A>G mutation affected the autophagy, we evaluated the mitophagic states of mutant and control cell lines by flow cytometry using Cyto-ID, a cationic amphilic tracer dye that labeled mitophagic compartments ( 69 , 70 ). Geometric mean intensity was measured for assessment of autophagy in each sample.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To investigate if the m.4295A>G mutation affected the autophagy, we evaluated the mitophagic states of mutant and control cell lines by flow cytometry using Cyto-ID, a cationic amphilic tracer dye that labeled mitophagic compartments ( 69 , 70 ). Geometric mean intensity was measured for assessment of autophagy in each sample.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty micrograms of total cellular proteins from various cell lines were electrophoresed, electroblotted and hybridized with LC3, p62 and with β -actin as a loading control. ( D ) Quantification of autophagy markers LC3 I/II and p62 in mutant and control cell lines were determined as described elsewhere ( 70 ). Three independent determinations were done in each cell line.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Blue native gel electrophoresis was performed by isolating mitochondrial proteins from various cell lines, as detailed elsewhere. 20,34 Samples containing 30 μg of mitochondrial proteins were separated on 3% to 11% Bis-Tris native polyacrylamide gel. The primary antibodies applied for this experiment were a totally human OXPHOS antibody cocktail with a voltage-dependent anion-selective channel (VDAC) as a loading control.…”
Section: Blue Native Gel Electrophoresismentioning
confidence: 99%
“…ited mild defects in complex I activity. [18][19][20] The incomplete penetrance and gender bias in patients presenting with optic neuropathy suggest a role for the nuclear modifier genes in the phenotypic expression of LHON-associated mtDNA mutations. 21 Our recent study demonstrated that several LHON families were manifested by synergic interaction between the m.11778G>A mutation and mutated modifiers YARS2 encoding mitochondrial tyrosyl-tRNA synthetase and X-linked modifier PRICKLE3 encoding a mitochondrial protein linked to biogenesis of ATPase.…”
mentioning
confidence: 99%